Investigation of mechanical stress-induced failure in transfer-bonded vertically aligned carbon nanotube arrays - Zhai, Yiming (Nanyang Technological University, 2023)
As society increasingly embraces the digital world, technological progress is inevitable. With the proliferation of technology, the demand for advanced electronic devices that are both high-performing and portable is rising. This presents a challenge in terms of protecting these devices from electromagnetic interference using conventional methods. Carbon nanotubes have been identified as a potential alternative material for electromagnetic shielding. However, directly synthesizing carbon nanotubes onto microelectronic devices is not practical due to the high temperature required. As a result, a new transfer technique for carbon nanotubes is being investigated. This project focuses on the characterisation and optimisation of a novel carbon nanotube transfer technique based on of mechanical stress-induced failure analyses. Scanning Electron Microscopy is utilized for characterization. Multiple process parameters such as growth duration, etch durations, thickness of gold, spacer height and spacer material choices are examined throughout this project. In conclusion, the results of conductivity and bonding strength are analyzed and discussed.